BBIPS : a blackboard based intergrated process supervision - Oh, Kok Wee (2008)
The research effort undertaken by the author attempts to investigate the use of the blackboard architecture to realize the Integrated Process Supervision paradigm in a heterogeneous control environment that supports dynamic switching of control regimes and their corresponding techniques.